REDESAIN PERENCANAAN STRUKTUR HOTEL CITY ONE JALAN VETERAN SEMARANG - Aldyan Wingga Okiyarta; Fajar Nurjihad Cristian; Parang Sabdono; Windu Partono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
City One Hotel lies at Veteran road, Semarang city. This hotel is built at less large area so vehicle come in and sticking out floor basement becomes distress. This redesign change distance between columns from 6 meters become 8 meters, so vehicle comes in and sticking out floor basement become easier. Redesign of the Structure of City One Hotel is make parking area more wider. Parking area from first design only use 1st basement and 2nd basement, meanwhile result of redesign use 1st basement, 2and basement and 2bth basement. First design of City One Hotel used Double System with Intermediate Moment Resisting Frames (IMRF), meanwhile redesign use Double System with Special Moment Resisting Frames (SMRF) for it structure system. This redesign based SNI 1726-2012, and value of earthquake parameter response was download from website of Ministry of Public Work for Semarang City. In order to easier modelling and building structure analysis, redesign of City One Hotel are helped by SAP.2000 version 12 and CSI Col progam. The other differences between first design and redesign’s result is cross-sectional shape of the column and sectional area of the beam. First design use rectangular cross-sectional shape column, meanwhile redesign use square cross-sectional shape column. Benefit of square cross-sectional shape column is moment of inertia equally strong for both sides. The redesign’s beam sectional area is wider than before, this is because increased load on beams comparable with increasing distance between columns.